Control Against Armyworm Caterpillars on the Coastal of the Rio Nunez-Boke, Republic of Guinea - Mamadou, Gandéka; Niaz, Ali; Ratemo, Billy; Nevame, Adedze Yawo Mawunyo; Camara, Lansana Mariama; Camara, Jean Pierre (Journal of Asian Scientific Research, 2015)
This study was conducted to test the effects of soap and branches of coconut trees on the caterpillars. Armyworms cause great economic losses to farmers of the Rio Nunez region in Guinea. They destroy culture and cause irritation to farmers. In fact, armyworms cause very serious allergic reactions on the skin of sensitive individuals. That is why efforts are often put in place to eliminate or at least reduce the adverse effects of these caterpillars. The larvae or caterpillars feed on green matter during the early stages of their development before moving on to the cultivated rice. Young larvae eat the lower epidermis of the leaves and thus protect themselves. Sometimes shoot tips are attacked thus leading to the total destruction of fields especially nurseries. These caterpillars live in colonies for 1 month before dispersing in the plains and surrounding fields. Therefore, this is the best period for fighting them. Finding effective methods to control their activities has become imperative to preserve the culture of farmers in these areas.